The external signaling of facedes in the current urban context of the city of São Paulo - Fernandes, Vitor de Castro; Prado, Gilbertto (DAT Journal, 2021)
This research proposes an exploratory investigation of the behavior of brands in the urban context of the city of São Paulo. For this purpose, it is initially intended to understand the configuration of the elements that make up a system of visual identity. Because it is an approach related to the city of São Paulo, the urban context and its environmental perception will be studied, considering the changes that have taken place in the landscape of São Paulo due to the accelerated growth of the metropolis in the last decades. In this sense, it is opportune to lift the restrictions imposed by the Lei Cidade Limpa in force in the municipality a decade ago. Finally, in order to illustrate the relation of the signaling of the marks in the city, a study of the external identifications of commercial establishments will be carried out in order to understand the aesthetic resources used in the elements that surround the visual communication projects of its façades, considering the restrictions imposed by the Law.